EFFECTS OF ANABOLIC-ANDROGENIC STEROIDS ON MENTAL HEALTH - COMPREHENSIVE REVIEW - Mateusz Kosowski; Wiktor Śliwiński; Karolina Zarówna; Daniel Chołuj; Jakub Marciniak; Jakub Mazur; Weronika Pura; Dominika Matecka (International Journal of Innovative Technologies in Social Science, 2026)
This review summarizes current information on the mechanisms and adverse outcomes of anabolic-androgenic steroid (AAS) usage. Chronic use of AAS induces significant structural and functional changes in the brain, especially in the prefrontal cortex, hippocampus, and amygdala, through monoaminergic and GABAergic dysregulation, alterations in the tryptophan-kynurenine pathway, and neuroinflammation. Moreover, abuse of AAS causes remodeling of fronto-limbic circuits, as well as suppression of the hypothalamic-pituitary-gonadal (HPG) axis. Clinically, excessive AAS consumption is associated with psychotic, depressive, and anxiety-related symptoms, cognitive decline, and increased aggressive behaviors.